Integração de DAW com Infraestruturas Remotas de Processamento de Áudio - Batista, Carlos E. C. F.; Andrade, Gabriel B. F.; Lima, Geovana M. S.; Guedes, Caio M. C. (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2024)
This article introduces Orchestrator Pad, an open-source audio processing plug-in built using JUCE, designed to facilitate access to the capabilities of the Music.AI platform. This service offers advanced features such as stem separation, automatic mastering, and various other forms of audio manipulation through a REST API. It supports the creation of custom workflows that integrate its services, seamlessly invoked by the plug-in using a C++ wrapper library developed in parallel. After remote audio processing, the resulting files can be played within any compatible DAW through the plug-in. This paper details the plug-in's architecture and core functionalities and discusses the advantages of incorporating AI-driven workflows into music production environments. The project repository provides the necessary code and configuration for building the Orchestrator Pad plug-in as either a standalone application or a VST plug-in.